Direct Chosen-Ciphertext Secure Attribute-Based Key Encapsulations without Random Oracles - Blömer, Johannes; Liske, Gennadij
We present a new technique to realize attribute-based encryption (ABE) schemes secure in the standard model against chosen-ciphertext attacks (CCA-secure). Our approach is to extend certain concrete chosen-plaintext secure (CPA-secure) ABE schemes to achieve more efficient constructions than the known generic constructions of CCA-secure ABE schemes. We restrict ourselves to the construction of attribute-based key encapsulation mechanisms (KEMs) and present two concrete CCA-secure schemes: a key-policy attribute-based KEM that is based on Goyal's key-policy ABE and a ciphertext-policy attribute-based KEM that is based on Waters' ciphertext-policy ABE. To achieve our goals, we use an appropriate hash function and need to extend the public parameters and the ciphertexts of the underlying CPA-secure encryption schemes only by a single group element. Moreover, we use the same hardness assumptions as the underlying CPA-secure encryption schemes.

Attributbasierte Verschlüsselung mittels Gittermethoden - Mathematische Grundlagen, Verfahren und Sicherheitsbeweise - Kohn, Kathlén

StreamKM++: A clustering algorithm for data streams - Ackermann, Marcel Rudolf; Märtens, Marcus; Raupach, Christoph; Swierkot, Kamil; Lammersen, Christiane; Sohler, Christian

Turing und Kryptografie - Blömer, Johannes (Informatik-Spektrum)
Ich beschreibe die deutsche Enigma-Verschlüsselungsmaschine und skizziere, wie sie von den Codebrechern von Bletchely Park um Alan Turing gebrochen wurde. Besonderes Augenmerk lege ich auf die Beiträge Alan Turings und die Bedeutung seiner Leistung für die Entwicklung moderner Kryptografie.

Identitätsbasierte Signaturen - Ein Sicherheitsbeweis für Signaturen auf Grundlage von Gap-Diffie-Hellman-Gruppen mit Hilfe des Forking-Lemmas - Löken, Nils

Identitätsbasierte Kryptographie - Implementierung von Paarungen für Körper der Charakteristik 2 - Haarhoff, Thomas

Attribute-basierte Verschlüsselung - Schleiter, Patrick

Bicriteria-Approximation für das k-Median-Clustering mit Bregman-Divergenzen - Böttger, Timm

The Monotone Complexity of Computing k-Clique on Random Graphs - Märtens, Marcus

Algorithms for lattice problems with respect to general norms - Naewe, Stefanie